2016
DOI: 10.18632/oncotarget.11853
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of C-reactive protein, interleukin-6 and tumor necrosis factor-α and risk of colorectal adenomas: a meta-analysis

Abstract: Results from publications on inflammatory markers of C-reactive protein (CRP), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) and risk of colorectal adenomas are not consistent. A meta-analysis was conducted to explore the above-mentioned associations. Relevant studies were identified by a search of Embase, Medline and PubMed through February 2016. A random effect model was adopted to combine study-specific odds ratio (OR) and 95% confidence interval (95% CI). Between-study heterogeneity and publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
11
0
3
Order By: Relevance
“…Given the high levels of IL‐6 produced in TSG‐6 −/− ‐MSCs, it was of interest to determine whether the loss of TSG‐6 could sustain pro‐tumoral effects of MSCs. To investigate this possibility, we exploited the effect of MSCs on tumor development in a colitis‐associated model of CRC in which IL‐6 has profound impact on tumorigenesis . Interestingly, we observed that mice receiving allogeneic TSG‐6 −/− ‐MSCs displayed a significant increased number of tumor lesions compared with either untreated (phosphate‐buffered saline [PBS]) or WT‐MSCs‐treated groups, as determined by endoscopic and histological recordings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the high levels of IL‐6 produced in TSG‐6 −/− ‐MSCs, it was of interest to determine whether the loss of TSG‐6 could sustain pro‐tumoral effects of MSCs. To investigate this possibility, we exploited the effect of MSCs on tumor development in a colitis‐associated model of CRC in which IL‐6 has profound impact on tumorigenesis . Interestingly, we observed that mice receiving allogeneic TSG‐6 −/− ‐MSCs displayed a significant increased number of tumor lesions compared with either untreated (phosphate‐buffered saline [PBS]) or WT‐MSCs‐treated groups, as determined by endoscopic and histological recordings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 This practice is largely unsupported by evidence; inflammatory markers are not recognised within current guidelines for cancer diagnosis, 8 with the exception of myeloma, where first line tests include ESR or PV. Cohort studies in the general population (irrespective of symptoms) have examined the association between raised CRP and risk of future cancer, 911 including meta-analyses of the risk of future colorectal, 12,13 lung, 14 ovarian 15 and breast cancer. 16,17 However, the associations are not strong enough to be clinically useful for identification of symptomatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Association between chronic inflammation and the risk of colorectal cancer remains controversial. Several recent meta-analyses showed no evidence of the association between circulation level of TNF-α and the risk of colorectal cancer [38,39].…”
Section: Discussionmentioning
confidence: 99%